Colección Alfa Romeo de Dibujos de Arquitectos - Glusberg, Jorge; Rattazzi, Cristiano (Buenos Aires : MNBA - Museo Nacional de Bellas Artes Buenos Aires, 1998)
Altuna, Enrique ; Alvarez, Mario Roberto ; Ambasz, Emilio ; Ando, Tadao ; Andreu, Paul ; Angel, Patricia ; Miglioni, Viviana ; Turrillo, Gabriel ; Horacio Angilletta & Asociados ; Ezcurra, Aslan y ; Bach, Jaume ; Mora, Gabriel ; Baracco, Juvenal ; Baudizzone, Miguel ; Varas, Alberto ; Lestard, Jorge ; Behnisch, Günter ; Bellini, Mario ; Benadon, Ricardo Sule ; Berdichevsky, Carlos Alberto ; Cherny, Rubén ; Besfamille, Carlos ; Rojo, Juan Manuel ; Biquard ; Marjovsky ; Urruty ; Bischof, Bernardo ; Egozcue, Maria Teresa ; vidal, Guillermo ; Blinder, Ricardo ; Janches, Flavio ; Bodas, Martin ; Miani, Rodolfo ; Alejandro Anger & Asociados ; Borta, Mario ; Bruno, Luis ; Aisiks, Laura ; Bruno, Maria ; Bruno, Luis ; Solessio, Daniel ; Bacza, Alberto Campo ; Tiscornia, Camps Y ; Canella, Guido ; Casano, Maria ; Zubillaga, Alfredo F. ; Poli, Juan Carlos ; Casellas, Sergio O. ; Conticello-Chami ; Converti, Roberto ; Aiello, Mario Corea ; Cordeyro, Enrique ; Correa, Charles ; Ruiz, Federico Correa ; De Silva, Walter Maria ; Diaz, José Ignacio ; Diez, Fernando ; Folch, Emilio Donato ; Döring, Wolfgang ; Dujovne, Bernardo ; Hirsch y Asociados ; England, Richard ; Erickson, Arthur ; Fainsilber, Adrien ; Faivre, Mederico ; Roman, Norma ; Terry Farrell & Partners ; Fernández Prieto & Asociados ; Fervenza, Juan Carlos ; Forero, Laureano ; Carlos Fourmentel & Asociados ; Glaser, Milton ; Goldman, Mario ; Luengo, Emilio Gómez ; de León, Teodoro González ; Graafland, Arie ; Grimshaw, Nicholas T. ; Grinberg, Jaime ; Dwek, Adriana ; Sartorio, Gustavo ; Iglesias, Julio ; Gwathmey-Siegel & Asociados ; Hafner, Bernhard ; Hampton-Rivoira y Asociados ; Hejduk, John ; Hertzberger, Herman ; Herzog & de Meuron ; Isozaki, Arata ; Jahn, Helmut ; Kikutake, Kiyonori ; etc.
biografie
Engels & Spaans
boek
Keywords: Brazilië